Definitions, signs, and symptoms of constipation in people with severe or profound intellectual disabilities: A systematic review. Issue 5 (May 2022) - Wagenaar, Marjolijn C.; van der Putten, Annette A.J.; Douma, Johanna G.; van der Schans, Cees P.; Waninge, Aly
Abstract: Background: It is difficult to diagnose constipation for people with severe or profound intellectual disabilities. Definitions for this are ambiguous, and the symptoms and signs are often unnoticed. The aim of this study is to identify clear definitions of constipation for people with different levels of intellectual disabilities and to identify signs and symptoms. Method: Guided by the PRISMA statement, a systematic review of the literature was conducted within electronic databases MEDLINE, Embase, CINAHL, Cochrane, and PsycINFO. Definitions, signs, and symptoms were extracted and the quality of definitions was assessed. Results: In total, 24 studies were included. Quality of definitions ranged from poor to good quality. Standard and referenced definitions were used in ten studies, a self-composed definition was employed in eleven studies; and three studies did not refer to a source of the definition. The self-composed definitions had not been evaluated after being used for the target group, and no scientific substantiation was available. A broad range of signs and symptoms were described. Conclusions: No substantiated definition has been ascertained for constipation for people with severe or profound intellectual disabilities. Further research will be necessary to identify which signs and symptoms are important for defining constipation in this target group. Abstract : Intellectual Disabilities; Severe or profound; Constipation; Definition; Signs and symptoms; Systematic Review